'Angelakisella massiliensis' gen. nov., sp. nov., a new bacterial species isolated from human ileum. (March 2017) - Mailhe, M.; Ricaboni, D.; Vitton, V.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We present here a summary of the main characteristics of ' Angelakisella massiliensis ' strain Marseille-P3217 T (= CSUR P3217) that was isolated from the ileum liquid sample of a 76-year-old woman.